Applying the resource-based view to alliance formation in specialized supply chains. Issue 3 (21st August 2017) - Steiner, Bodo; Lan, Kevin; Unterschultz, Jim; Boxall, Peter
Abstract : Purpose: The purpose of this paper is to explore drivers of alliance formation in a specialized supply chain from a manager's perspective, focussing on firm-specific resources, resources embedded in inter-firm relationships and capabilities under the control of the focal firm. Design/methodology/approach: This paper focusses on the resource-based view to obtain insights from the analysis of a manager survey conducted in Canada's beef sector, applying a logistic regression approach to study alliance formation. Findings: In identifying significant roles for resource richness and diversification of resource usage, the analysis highlights the importance of resource characteristics underlying factor market imperfections as drivers of alliance formation in a single primary input supply chain. The results suggest that resource heterogeneity is important for alliance formation and organizational success in specialized supply chains. Research limitations/implications: If previous alliance-related experience of managers, controlled for in the underlying cross-sectional survey, serves as an approximation for persistent unobservables impacting the alliance formation decision, we may face spurious state-dependence. Practical implications: Managers interested in building compatible alliances in specialized single primary input supply chains may benefit from an improved understanding of the differential role of resource characteristics and resource heterogeneity for alliance formation, as these can function as a source of competitive advantage. Originality/value: The analysis provides new insights from an individual manager's perspective on alliance formation drivers in a specialized agri-food supply chain, thereby solidifying extant findings on alliance formation obtained in other sectors. The study contributes to the understanding of the role of resources in alliance formation with regard to prior relationship experience, resource heterogeneity and thus causal ambiguity, thereby also contributing to the debate of the role of relational capabilities vs firm-internal resources for sustained competitive advantage.